Environmental Exploitation and Tourism Commercialization: The Transformation of Sibolangit Camping Ground - Benedito Larryos Panjaitan; Vania Pramudita Hanjani (Sabda: Jurnal Kajian Kebudayaan, 2026)
Sibolangit Camping Ground in North Sumatra has undergone a significant transformation from a natural forest into a commercial tourism destination. This study aims to analyze the environmental and social impacts of tourism commercialization and land-use change in the area. A qualitative descriptive approach was employed through field observations and literature review to examine the relationship between local economic interests, environmental exploitation, and community social dynamics. The findings reveal that rapid and unregulated development—such as deforestation for villas, small-scale commercial facilities, and camping infrastructure—has led to ecological degradation, including rising temperatures, declining environmental quality, and waste accumulation. Furthermore, tourism commercialization has triggered various social issues, including land ownership conflicts, unhealthy business competition, and the emergence of deviant activities. These dynamics reflect the pattern of the Tragedy of the Commons, where shared natural resources are overexploited for short-term economic gain. This study highlights the urgency of implementing sustainable and community-based tourism management to balance economic benefits with environmental conservation. Therefore, stronger regulatory frameworks, increased local awareness, and multi-stakeholder collaboration are essential to preserve the ecological and social sustainability of Sibolangit as a nature-based tourism destination.